THE EFFECT OF UNEMPLOYMENT, ECONOMIC GROWTH, LEVEL OF EDUCATION ON THE HUMAN DEVELOPMENT INDEX WITH POVERTY AS MEDIATION - Hannan, Zainul; Jacob, Jufri; Niam, Siti Khozinatun; Dewi, Susantriana; Nashih, Muhammad (ITB AAS Indonesia Surakarta, 2024)
The Human Development Index is an internationally agreed indicator of the success of a region of a country to assess the quality of human development in terms of its impact on health, education, and people's standard of living. This study aims to examine the factors of the unemployment rate, economic growth, education level, and poverty rate on the human development index in 33 Indonesian provinces in 2011-2020 using secondary data sourced from the Central Statistics Agency (BPS). The method used is path analysis which is processed using the SmartPLS3 application. The results of this study indicate that the unemployment rate, economic growth, education level, and poverty rate directly have a significant effect on the human development index. Whereas in the indirect relationship the poverty variable can only mediate between the level of education and the human development index. Keyword: Unemployment Rate, Economic Growth, Education, Poverty, and Human Development Index